Electrochemical Fabrication of rGO-embedded Ag-TiO2 Nanoring/Nanotube Arrays for Plasmonic Solar Water Splitting - Sang, Lixia; Lei, Lei; Burda, Clemens (Nano-Micro Letters, 2019)
Effective utilization of hot electrons generated from the decay of surface plasmon resonance in metal nanoparticles is conductive to improve solar water splitting efficiency. Herein, Ag nanoparticles and reduced graphene oxide (rGO) co-decorated hierarchical TiO2 nanoring/nanotube arrays (TiO2 R/T) were facilely fabricated by using two-step electrochemical anodization, electrodeposition, and photoreduction methods. Comparative studies were conducted to elucidate the effects of rGO and Ag on the morphology, photoresponse, charge transfer, and photoelectric properties of TiO2. Firstly, scanning electron microscope images confirm that the Ag nanoparticles adhered on TiO2 R/T and TiO2 R/T-rGO have similar diameter of 20 nm except for TiO2 R-rGO/T. Then, the UV–Vis DRS and scatter spectra reveal that the optical property of the Ag-TiO2 R/T-rGO ternary composite is enhanced, ascribing to the visible light absorption of plasmonic Ag nanoparticles and the weakening effect of rGO on light scattering. Meanwhile, intensity-modulated photocurrent spectroscopy and photoluminescence spectra demonstrate that rGO can promote the hot electrons transfer from Ag nanoparticles to Ti substrate, reducing the photogenerated electron–hole recombination. Finally, Ag-TiO2 R/T-rGO photoanode exhibits high photocurrent density (0.98 mA cm−2) and photovoltage (0.90 V), and the stable H2 evolution rate of 413 μL h−1 cm−2 within 1.5 h under AM 1.5 which exceeds by 1.30 times than that of pristine TiO2 R/T. In line with the above results, this work provides a reliable route synergizing rGO with plasmonic metal nanoparticles for photocatalysis, in which, rGO presents a broad absorption spectrum and effective photogenerated electrons transfer. Highlights: 1 Reduced graphene oxide (rGO) in electrode can weaken the light scattering of plasmonic Ag nanoparticles and promote the hot electrons transfer from Ag nanoparticles to Ti substrate. 2 A route synergizing rGO with plasmonic Ag on TiO2 for plasmonic solar water splitting was provided.